2018
DOI: 10.3892/etm.2018.6633
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status of cardinal ligament in pelvic organ prolapse

Abstract: Pelvic organ prolapse (POP) is a common and distressing health problem in adult women, but the pathophysiological mechanism is yet to be fully elucidated. Previous studies have indicated that oxidative stress may be associated with POP. Thus, the aim of the present study was to investigate the oxidative status of pelvic supportive tissue in POP and further demonstrate that oxidative stress is associated with the pathogenesis of POP. A total of 60 samples were collected from females undergoing hysterectomy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 102 publications
0
21
0
2
Order By: Relevance
“…A further study concluded that mechanical strain may activate the PI3K/AKT-mediated OS signaling pathway, thereby promoting the apoptosis and senescence of pelvic fibroblasts, and reducing the production of collagen (36). A subsequent study also confirmed this notion (37). Furthermore, reduced OS has been indicated to promote collagen synthesis, while its overexpression may interfere with the homeostasis and metabolism of ECM by affecting the levels of MMPs/TIMPs and the activation of the TGF-β1/Smad signaling pathway, which in turn results in induction of POP (38).…”
Section: Os and Popmentioning
confidence: 79%
“…A further study concluded that mechanical strain may activate the PI3K/AKT-mediated OS signaling pathway, thereby promoting the apoptosis and senescence of pelvic fibroblasts, and reducing the production of collagen (36). A subsequent study also confirmed this notion (37). Furthermore, reduced OS has been indicated to promote collagen synthesis, while its overexpression may interfere with the homeostasis and metabolism of ECM by affecting the levels of MMPs/TIMPs and the activation of the TGF-β1/Smad signaling pathway, which in turn results in induction of POP (38).…”
Section: Os and Popmentioning
confidence: 79%
“…Apart from the hyperglycemic environment, the formation process of AGEs also accelerates under chronic inflammation or oxidative stress conditions (31,32). Previous studies have reported that ROS increase in POP (33,34), interfering with multiple cellular processes and favoring POP development. Thus, we speculate that the high level of AGEs in the prolapse tissues could result from increased ROS in POP because the formation of AGEs accelerates under the elevated ROS level in prolapse tissues (35).…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) is a phenomenon that pelvic organs such as uterus, vagina, bowel and bladder leave out of their normal anatomical location, resulting in a serious of functional disorders [ 1 ]. It is a very frequent disease in postmenopausal women, especially in senile females [ 2 ].…”
Section: Introductionmentioning
confidence: 99%